Eusebius of Caesarea and the Testimonium Flavianum (Josephus, Antiquities, XVIII. 63f.) - Wallace-Hadrill, D. S. (The journal of ecclesiastical history, 1974)
The case against the authenticity of the Testimonium was put succinctly by Benedict Niese, ‘nam scriptus est a Christiano, male cohaeret cum insequentibus, dicendi genus a Josepho alienus, ab antiquissimis scriptoribus Christianis, imprimis Origine, non agnoscitur, abest ab argumentis libri XVIII, non exstat in Bello Judaico, neque ulla est causa cur necessarium putemus'. Scholarly opinion has long been divided over the matter, but it is safe to say that the arguments against authenticity outweigh those that would retain the passage as Josephan. Niese's points, that the passage interrupts a series of notices of Jewish risings and revolts and that Origen appears to have known Josephus only as hostile to Christianity, can be supplemented by the difficulty of attributing apparently Christian sentiments to a writer who in his last work, Contra Apionem, was very plainly proud to be a Jew. But if the passage is an interpolation, the further question is posed, whether it was inserted into the text of Josephus as a complete unit or whether it is the result of a process of minor alterations by many hands over many years. Here again there is divergence of opinion, but since 1930 it has been difficult to maintain the simple view of a single interpolation by one man at one time. Robert Eisler's attack upon this simple view was made possible by the publication of a thirteenth-century Slavonic version of Josephus initiated by A. Berendts, who in an earlier work had traced the Christian interpolations in Josephus back to the first century. Eisler's general contention, that the authentically Josephan basis of the passage constituted a hostile notice of Christianity and that this had, been altered in many particulars by various hands to show the opposite of what Josephus had written, was cautiously defended by Thackeray, the doyen of English-speaking Josephan scholars, in his Hilda Stich Strook lectures at the Jewish Institute of Religion.